Methylation of Exons 1(D), 1(F), and 1(H) of the Glucocorticoid Receptor Gene Promoter and Exposure to Adversity in Pre-School Aged Children - Tyrka, Audrey R. (Dev Psychopathol, 2015)
Epigenetic modifications to the genome are a key mechanism involved in the biological encoding of experience. Animal studies and a growing body of literature in humans have shown that early adversity is linked to methylation of the gene for the glucocorticoid receptor (GR) which is a key regulator of the hypothalamic-pituitary-adrenal (HPA) axis as well as a broad range of physiological systems including metabolic and immune function. One hundred eighty-four families participated, including n=74 with child welfare documentation of moderate-severe maltreatment in the past six months. Children ranged in age from 3 to 5 years, and were racially and ethnically diverse. Structured record review and interviews in the home were used to assess a history of maltreatment, other traumas, and contextual life stressors, and a composite variable assessed the number exposures to these adversities. Methylation of regions 1(D), 1(F), and 1(H) of the GR gene was measured via sodium bisulfite pyrosequencing. The composite measure of adversity was positively correlated with methylation at exons 1(D) and 1(F) in the promoter of NR3C1. Individual stress measures were significantly associated with a several CpG sites in these regions. GR gene methylation may be a mechanism of the bio-behavioral effects of adverse exposures in young children.